2010
DOI: 10.1007/s00018-009-0246-5
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α modulates the migratory response of mesenchymal stem cells to TRAIL

Abstract: The number of circulating mesenchymal stem cells (MSC), analyzed after acute myocardial infarction (AMI), was lower in AMI patients who developed heart failure (HF) in the follow-up. Conversely, the circulating levels of tumor necrosis factor (TNF)-alpha, and osteoprotegerin (OPG) were higher in AMI patients who developed HF with respect to the patients who did not develop HF. In vitro exposure to TNF-alpha enhanced the migration of MSC in response to TNF-related apoptosis-inducing ligand (TRAIL) and significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Our group has recently shown that TRAIL is able to promote the migration of BM-MSC in vitro [26]. OPG dose dependently neutralizes the promigratory activity of TRAIL [27], so the high levels of OPG observed in diabetic patients might impair the pro-migratory signalling driven by TRAIL, accounting for the abnormalities of BM-SC in DM. …”
Section: Rationale For the Use Of Adult Stem/progenitor Cells For mentioning
confidence: 99%
“…Our group has recently shown that TRAIL is able to promote the migration of BM-MSC in vitro [26]. OPG dose dependently neutralizes the promigratory activity of TRAIL [27], so the high levels of OPG observed in diabetic patients might impair the pro-migratory signalling driven by TRAIL, accounting for the abnormalities of BM-SC in DM. …”
Section: Rationale For the Use Of Adult Stem/progenitor Cells For mentioning
confidence: 99%
“…They are considered to reside in specific areas of each tissue and remain inactive for long periods of time, until they are activated by signals indicating that more cells are required to maintain tissue integrity, or by signals from sites of tissue injury. Different cytokines and growth factors are recruited in stem cell fate regulation, including quiescence, self-renewal, differentiation, apoptosis and mobilization from their original niche (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…TNFα might synergize with IFN‐γ in regulating gene expression in MSCs [Xu et al, 2009]. TRAIL is another member of TNF family and it induces significantly human MSC migration and TNF‐α may modulate this course [Corallini et al, 2010]. However, the question whether or not other members of TNF family, such as LIGHT, activate MSCs remains unclear currently.…”
mentioning
confidence: 99%